HAK ASASI MANUSIA DAN TANTANGAN KESETARAAN GENDER DI INDONESIA TIMUR: REFLEKSI ATAS KASUS DISKRIMINASI PEREMPUAN DI KOTA KUPANG - Erwin Styven Aditya Tari; Fadil Mas'ud; Redemtoria Juana Sanbret; Diah Permata Rosalin Abineno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the role of human rights (HR) in eliminating gender discrimination and the challenges faced in achieving gender equality in Kupang City. Instances of discrimination against women in this area are still evident in the division of labor, promotion opportunities, and access to training, which generally favor men. The research employs a qualitative approach using in-depth interviews, observation, and document analysis, while data are analyzed thematically to identify patterns of discrimination. The findings reveal that structural factors such as suboptimal regulations, cultural factors including patriarchy and customary norms, and economic factors that place women in vulnerable positions are the main causes of persistent inequality. Gender mainstreaming programs in Kupang remain largely temporary projects, not integrated into routine budgets, and have yet to involve key actors such as traditional and religious leaders, thus limiting their social impact. The study also found that psychological barriers discourage some women from reporting discrimination due to fear of being disbelieved or facing negative reactions in the workplace. The conclusion emphasizes that gender equality policies in Kupang require a more comprehensive human rights-based reinforcement, encompassing institutional consistency, cultural transformation, and active participation from multiple stakeholders to minimize discrimination and achieve sustainable gender equality.